Distribution of 5-methylcytosine in chromatin. - Razin, A (1977)
The content of 5-methylcytosine in eukaryotic DNA was measured by mass spectrometry. Almost equal amounts of methylated cytosine were found in the DNA of various tissues of the chicken. When chromatin or nuclei were digested with micrococcal nuclease, 50% of the DNA was found to be nuclease resistant. In contrast to this, over 75% of the 5-methylcytosine was protected from nuclease digestion by chromatin proteins. These results suggest that 5-methylcytosine is nonrandomly distributed with respect to the nucleoproteins.